2015
DOI: 10.19182/remvt.20564
|View full text |Cite
|
Sign up to set email alerts
|

Qualité de la viande de dromadaire dans les abattoirs de Ouargla en Algérie. I. Quelques caractéristiques physico-chimiques de la viande au cours de la maturation

Abstract: Les paramètres physico-chimiques au cours de la maturation de quatre muscles (semitendinosus [ST], rectus femoris [RF], longissimus thoracis [LT] et semimembranosus [SM]), conservés à 4 °C, ont été mesurés chez des dromadaires mâles (10 jeunes de trois à quatre ans et 10 adultes de plus de cinq ans) de race Sahraoui. Une diminution de la température post mortem a atteint une valeur minimale de 5,7 ±  0,20  °C (LT) chez les adultes, alors que la valeur minimale enregistrée chez les jeunes a été plus basse avec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
2
2
1
1
Order By: Relevance
“…This finding agrees with those of Kim et al (2014), Strydom and Rosenvold (2014), who reported that high rigor mortis temperature in carcasses has negative effects on water-holding capacity and color stability, as well as muscle texture. In conflict with our findings, Benaissa et al (2014) observed a significant positive correlation between muscle temperature and waterholding capacity.…”
Section: Relationships Between the Different Parameterscontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding agrees with those of Kim et al (2014), Strydom and Rosenvold (2014), who reported that high rigor mortis temperature in carcasses has negative effects on water-holding capacity and color stability, as well as muscle texture. In conflict with our findings, Benaissa et al (2014) observed a significant positive correlation between muscle temperature and waterholding capacity.…”
Section: Relationships Between the Different Parameterscontrasting
confidence: 99%
“…Moreover, in studies on beef by Abril et al (2001) and Villarroel et al (2003) and on broilers by Bowker and Zhuang (2015), it was shown that meat with a higher pH had greater water-holding capacity than that with a low pH. These observations agree with those reported by Benaissa et al (2014) in dromedary camel. Indeed, the same authors described a significant positive correlation between the average muscle pH at different postmortem times and the water-holding capacity of the longissimus thoracis muscle.…”
Section: Relationships Between the Different Parameterssupporting
confidence: 87%
See 1 more Smart Citation
“…They report that after slaughter, the rate of pH drop in muscles is slower for males than females of cattles. Similar results were previously announced by Benaissa et al, (2014) and BENAISSA in 2016 on dromedary muscles of the Sahrawi population of 1 hour after slaughter at the Ouargla slaughterhouse and by Bendall in 1973, on cattles muscles. According to Seideman and Crouse (1986), the male animal's muscles have a higher percentage of slow oxidative fibers and less rapid glycolytic fibers.…”
Section: Discussionsupporting
confidence: 87%
“…According to Boudjellal et al, (2008), acidification of the muscle is considered as major determinant of meat quality. Benaissa et al, (2014) ISSN: 2456-1878 https://dx.doi.org/10.22161/ijeab.61. 23 191 obtaine that the evolution of post-mortem pH is characterized by a rapid drop during the first eight hours after slaughter, followed by a slowdown.…”
Section: Introductionmentioning
confidence: 99%